Isolation and Characterization of Human Adult Epithelial Stem Cells from the Periodontal Ligament. (November 2015) - Athanassiou-Papaefthymiou, M.; Papagerakis, P.; Papagerakis, S.
We report a novel method for the isolation of adult human epithelial stem cells (hEpiSCs) from the epithelial component of the periodontal ligament—the human epithelial cell rests of Malassez (hERM). hEpiSC-rich integrin-α6 +ve hERM cells derived by fluorometry can be clonally expanded, can grow organoids, and express the markers of pluripotency (OCT4, NANOG, SOX2), polycomb protein RING1B, and the hEpiSC supermarker LGR5. They maintain the growth profile of their originating hERM in vitro. Subcutaneous cotransplantation with mesenchymal stem cells from the dental pulp on poly-l -lactic acid scaffolds in nude mice gave rise to perfect heterotopic ossicles in vivo with ultrastructure of dentin, enamel, cementum, and bone. These remarkable fully mineralized ossicles underscore the importance of epithelial-mesenchymal crosstalk in tissue regeneration using human progenitor stem cells, which may have already committed to lineage despite maintaining hallmarks of pluripotency. In addition, we report the clonal expansion and isolation of human LGR5 +ve cells from the hERM in xeno-free culture conditions. The genetic profile of LGR5 +ve cells includes both markers of pluripotency and genes important for secretory epithelial and dental epithelial cell differentiation, giving us a first insight into periodontal ligament–derived hEpiSCs.